2016
DOI: 10.1007/s10571-016-0403-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Discloses Molecular and Cellular Events Related to Neuronal Differentiation in SH-SY5Y Neuroblastoma Cells

Abstract: Human SH-SY5Y neuroblastoma cells are widely utilized in in vitro studies to dissect out pathogenetic mechanisms of neurodegenerative disorders. These cells are considered as neuronal precursors and differentiate into more mature neuronal phenotypes under selected growth conditions. In this study, in order to decipher the pathways and cellular processes underlying neuroblastoma cell differentiation in vitro, we performed systematic transcriptomic (RNA-seq) and bioinformatic analysis of SH-SY5Y cells differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 65 publications
(68 reference statements)
6
44
0
Order By: Relevance
“…There are many lines of evidence showing the effect of RA-differentiation in SH-SY5Y regarding the evaluation of proliferation rates (Ross 1996;Pezzini et al 2016;Kunzler et al 2016). Previous studies have demonstrated that RAinduced differentiation can cause cell cycle arrest either in G1/G0 phase or in G2/M phase and a decrease in proliferation rates, which leads to terminal differentiation of neuroblastoma cells (Qiao et al 2012;Hämmerle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are many lines of evidence showing the effect of RA-differentiation in SH-SY5Y regarding the evaluation of proliferation rates (Ross 1996;Pezzini et al 2016;Kunzler et al 2016). Previous studies have demonstrated that RAinduced differentiation can cause cell cycle arrest either in G1/G0 phase or in G2/M phase and a decrease in proliferation rates, which leads to terminal differentiation of neuroblastoma cells (Qiao et al 2012;Hämmerle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Human neuroblastoma SH-SY5Y cells (catalog number #94030304 European Collection of Cell Cultures) were cultured in DMEM-High glucose medium supplemented with 15% Foetal Bovine Serum (FBS), 2 mM L-glutamine and 1% non-essential amino acids (all from Euroclone), at 37°C in humified atmosphere with 5% CO 2 , as described (Pezzini et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to recognize molecular signatures and functional modules connected with overexpressed CLN1 in human neuronal cellular system. We utilized SH-SY5Y neuroblastoma cells (differentiated into a neuronal-like phenotype, Pezzini et al, 2017 ) to overexpress wt CLN1 and a selection of disease related mutations previously detected in CLN1-affected children. The differentiated cell lines underwent whole transcriptomic profiling by RNA-seq, to identify differentially expressed genes (DEGs) which are functionally related to the overexpression of wild-type or mutated PPT1.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of human neuroblastoma cells with retinoic acid triggers their exit from the cell cycle and their differentiation into a neuron-like cell type (Sidell 1982, Pahlman, Ruusala et al 1984. While many studies have sought to understand genetic changes underlying this process, most have focused on transcript-level changes, with evaluation of shifts in protein abundance only studied on a case-by-case basis (Hanada, Krajewski et al 1993, Kaplan, Matsumoto et al 1993, Korecka, van Kesteren et al 2013, Pezzini, Bettinetti et al 2017). Here we used RP in this simple model system to study the role of uORF activity in regulating protein translation during neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%